ANALISIS JARINGAN KERJA PEMBANGUNAN RUMAH TYPE 64 PERUMAHAN ARISKO SAMARINDA - Biya, Leydi Finalia (EKONOMIA, 2019)
This study aim to find out and analyze the timing of type 64 housing contruction using network planning faster than the 90 working days determined by PT Arisko Samarinda which is not optimal processing time. This formulation of the problem in this study is whether the determination of the time of type 64 house construction using network planning is faster than the establishment of 90 working days of house construction type 64 by PT Arisko Samarinda ?.Method Research by conducting direct perception in development of house of type 64 at Housing Of Arisko Samarinda. Analyzer the used analysis of PERT and of Critical Path Method (CPM). Based on the results of the research and discussion it can be explained that the planning time type home building project 64 by PT. Arisko is considered not optimal, so the hypothesis is accepted. This matter is seen from opportunity of attainment of time goals of solving of the project of which is expected by company that is 90 workday become 63 workday with a normal fee of Rp.308.151.447, while showed willingness of consumer wish the project of development of house of type 64 finishing during 60 workday with addition of expense equal to Rp.308.656.677, additional costs are obtained from the sum of normal costs plus incremental costs. Time 63 from PT. Arisko and 60 workday of consumer, so that acceleration time become 3 time workday development of house of type 64 woke up by PT. Arisko Samarinda represent not optimal workmanship time, so the hypothesis is accepted.